Dihydrofolate reductase: low-resolution mass-spectrometric analysis of an elastase digest as a sequencing tool. - Morris,HR; Batley,KE; Harding,NC; Bjur,RA; Dann,JG; King,RW (Biochem J, 1974)
An elastase digest of a protein of unknown structure, dihydrofolate reductase, was studied by mass spectrometry. This soluble digest contained a large number of small peptides in different yields, within the ideal molecular-weight range (200-1200) for mixture-analysis mass spectrometry. Sequences of the major component peptides in the digest are reported.